2020
DOI: 10.1007/s11036-020-01681-6
|View full text |Cite
|
Sign up to set email alerts
|

An Image Super-Resolution Reconstruction Method with Single Frame Character Based on Wavelet Neural Network in Internet of Things

Abstract: The application of the traditional single frame character image super-resolution reconstruction method has some problems, such as noise can not be removed completely and anti-interference performance is poor. A new method for the super-resolution reconstruction of single frame character image based on wavelet neural network is proposed. The structure and interface of image acquisition unit of solid state image sensor are designed. Combined with pinhole imaging model and camera self-calibration, image acquisiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Network Algorithm. Fuzzy neural network is the product of combining fuzzy theory with neural network, which brings together the advantages of neural network and fuzzy theory and integrates learning, association, recognition, and information processing [24][25][26][27][28][29][30][31].…”
Section: Research Design Of Music Teaching Assessment Model In Colleges and Universities Under Compensated Fuzzy Neuralmentioning
confidence: 99%
“…Network Algorithm. Fuzzy neural network is the product of combining fuzzy theory with neural network, which brings together the advantages of neural network and fuzzy theory and integrates learning, association, recognition, and information processing [24][25][26][27][28][29][30][31].…”
Section: Research Design Of Music Teaching Assessment Model In Colleges and Universities Under Compensated Fuzzy Neuralmentioning
confidence: 99%
“…e development of the deep learning algorithm is also at the forefront of the world [23]. Many researchers mainly analyse the performance of the deep learning algorithm and shallow neural network algorithm in the research of digital recognition [24][25][26][27][28]. Subsequently, it is confirmed that the deep belief network has great applicability and high efficiency.…”
Section: Related Workmentioning
confidence: 99%
“…In the image processing field, multi-focus-image-fusion is a significant branch [ 1 , 2 , 3 ]. Multi-focus-image-fusion is the process of combining two or more images with different focal points of the same scene into a composite image with all-focus, which is of service to humans and machine perception [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%